Analisis Faktor-Faktor Dalam Meningkatkan Minat Beli Dimediasi oleh Fomo: (Studi Pada Konsumen Kosmetik Focallure Yang Melakukan Pembelian Pada TikTokShop di Kabupaten Sukabumi) - Septiawati, Ika Teguh; Amal, Muhammad Khairul; Lestari, Nurni Arrina (Jurnal Ilmu Manajemen Retail Universitas Muhammadiyah Sukabumi, 2025)
This study aims to examine the impact of social media, viral marketing, and influencers on purchase intention, with fear of missing out (FOMO) as an intermediary variable among TikTok users of Focallure cosmetics in Sukabumi Regency. A quantitative approach was used by distributing questionnaires to 120 individuals who had purchased Focallure products more than twice. Data processing was carried out using AMOS software using the Structural Equation Modeling (SEM) method. The results showed that social media, viral marketing, and influencers contributed significantly to influencing FOMO. Furthermore, FOMO, social media, viral marketing, and influencers were proven to significantly influence consumer purchase intention. These findings indicate that emotional drives such as FOMO, which are influenced by digital marketing strategies, play a significant role in shaping consumer purchasing decisions. Therefore, a marketing communication strategy that emphasizes emotional and social aspects is key to increasing consumer purchase intention.